Use of satellite telemetry data, GIS, and HTML to create an interactive display of caribou movements - Prichard, Alexander K.; Carroll, Geoffry M.; George, John C.; Murphy, Stephen M.; Smith, Mike D.; Suydam, Robert S.; Yokel, David A. (Rangifer, 2003)
The use of animation clearly reveals the large annual variation in wintering areas and large differences in daily movement rates for this herd. This interactive display can be adapted for school groups, subsistence hunters, the general public, or scientists.